Convergence of the $q$ Analogue of Szász-Beta-Stancu Operators (Analysis in Theory and Applications, 2017)
In the present paper, we propose the $q$ analogue of Szász-Beta-Stancu operators. By estimate the moments, we establish direct results in terms of the modulus of smoothness. Investigate the rate of point-wise convergence and weighted approximation properties of the $q$ operators. Voronovskaja type theorem is also obtained. Our results generalize and supplement some convergence results of the $q$-Szász-Beta operators, thus they improve the existing results.